DEVELOPMENT OF THE TEA CULTIVATION ON THE TEA ROAD (for example Georgia) - Mamatova Mahfuza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article presents the history of the study of tea cultivation in Georgia, and examines these historical sources based on the reviews of various critical comparative sources. Also, various articles and monographs of O.Tatishvili, T.Sosesvili, B.Chkadua, Y.Stalinskii, Yersov, P.Gugushvili and K.Gabunii, who studied the history of tea cultivation in Georgia at the end of the 19th century, were analyzed.